MODERN IDEAS OF “SLOW SLEEP” AND “REM-SLEEP” AND THEIR ROLE IN PATHOGENESIS OF ALZHEIMER’S DISEASE (REVIEW OF LITERATURE) - I. M. Madaeva; O. N. Berdina (Acta Biomedica Scientifica, 2017)
This review discusses the data of new researches on the functional purpose of sleep and its stages, and its role in the development of pathological conditions. The main modern hypotheses and concepts about a role of slow sleep and REM-sleep (rapid eye movement) are interpreted. The visceral theory of slow sleep as an activator of restorative processes in the brain and manager of internal organs functions is described. A brain "drainage" function of slow sleep is known. Recent studies suggest sleep-wake disturbances, for example, obstructive apnea syndrome, may influence Alzheimer's disease (AD) onset and progression. Possible mechanisms such asfunctional disorders of brain lymphatic system during slow sleep and the extracellular accumulation of the amyloid-ß (Aß) peptide underlying the relationship between the sleep-wake disturbances and AD are described. The role of REM-sleep in the formation of the central nervous system in the early postnatal period and the performance of the function of mental adaptation are discussed. In this article, we presented data about the role both of neurotransmitters and neuropeptides in the regulation of sleep-wake cycle and the maintenance of wakefulness and REM-sleep. The possible new approach to the forecasting of cognitive and emotional-affective disorders in sleep disturbances is substantiated from the perspective of modern neuroscience and sleep neurophysiology still in childhood is justified.